Effect of κ-carrageenan on quality improvement of 3D printed Hypophthalmichthys molitrix-sea cucumber compound surimi product. (15th January 2022) - Yu, Wanying; Wang, Zheming; Pan, Yuxi; Jiang, Pengfei; Pan, Jinfeng; Yu, Chenxu; Dong, Xiuping
Abstract: In this study, κ-carrageenan was used as an additive to improve the quality of Hypophthalmichthys molitrix -sea cucumbers (HM-SC) compound surimi gel. The effects of κ-carrageenan on rheological properties, gel strength, textural and moisture characteristics, as well as microstructure of the HM-SC surimi gel were investigated, alongside with Fourier transform infrared (FT-IR) spectroscopic characterization and SDS-PAGE analyses of the compound materials. Rheological tests showed that addition of κ-carrageenan increased the storage modulus of the HM-SC compound materials in a dosage-dependent way, which led to superior shape-forming and shape-keeping abilities in 3D printed products. The best gel strength of 1236.04 g mm was obtained in samples with κ-carrageenan addition at 1.5% (w/w). The microstructure of the HM-SC compound surimi gel became more compact and denser, with improved connectivity. These samples also had reduced cooking loss and improved water holding capacity, confirmed by changes in water mobility characterized through Low-field nuclear magnetic resonance (LF-NMR). Moreover, κ-carrageenan addition did not change protein configuration much, neither was it contributed to the aggregation and degradation of proteins. These results showed that the quality of the HM-SC compound material could be improved with the κ-carrageenan addition, which could make it suitable for 3D printing based novel product development. Highlights: 3D printing technology for making HM-SC compound surimi product. κ-Carrageenan improves the quality of HM-SC compound surimi gel. κ-Carrageenan improves printability of HM-SC compound material.